Managing aggression in the emergency department: promoting an interdisciplinary approach - Rintoul, Y.; Wynaden, Dianne; McGowan, Sunita (Elsevier, 2009)
Incidents of aggression are frequent occurrences in hospitals, particularly the emergencydepartment. Aggression creates instability in the environment, impacts on patient careoutcomes and leads to increased levels of stress in staff. Regular exposure to aggression in theworkplace can have detrimental effects on health professionals' ongoing quality of life. Theemergency department is a gateway to care and is heavily populated 24 h a day. Therefore,it is essential that all health professionals are confident and well prepared to manage aggression.Based upon a review of the literature this paper outlines the causes of aggression and providesan interdisciplinary action plan for intervening with aggressive patients in the emergencydepartment. The importance of interdisciplinary ownership and the well planned managementof aggression are outlined.When well managed, the impact of aggression can be limited. Stability in the emergencydepartment ensures that health professionals can be responsive to the community's needsfor emergency care. This leads to the provision of effective and timely care and a stable workenvironment for all health professionals.